2020
DOI: 10.1002/ijgo.13326
|View full text |Cite
|
Sign up to set email alerts
|

Effect of misoprostol with and without letrozole on the induction of abortion for women with first‐trimester missed abortion

Abstract: Objective: To determine whether addition of letrozole to a misoprostol-based abortion regimen can increase the rate of complete abortion. Methods: The randomized, placebo-controlled, double-blind trial enrolled women with missed abortion in the first trimester of pregnancy attending Sadooghi Hospital, Isfahan, Iran, from 2016 to 2018. The women were randomly assigned to the study group, which received 10 mg of letrozole daily for 3 days, followed by two doses of 800 μg of vaginal misoprostol at a 4-hour interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Clearance is the main treatment for MA, but the death of the embryo absorbs a large amount of amniotic fluid causing organization of the tissue, and the necrotic tissues may form a tight connection with the uterine wall and cannot be completely detached from the uterine wall, which can lead to difficulty in scraping or hemorrhage after the scraping procedure [ 3 ]. If the pregnancy tissue remains in the uterine cavity for a longer period of time, it can also lead to tissue lysis and release of large amounts of hemolysin into the blood circulation of the pregnant woman, causing a coagulation disorder, which can cause massive uterine bleeding and even lead to diffuse intravascular coagulation [ 4 ]. Therefore, the use of medications or other treatments to promote the release of mechanized placental tissue from the uterine wall prior to cleansing surgery becomes crucial in the treatment of MA.…”
Section: Introductionmentioning
confidence: 99%
“…Clearance is the main treatment for MA, but the death of the embryo absorbs a large amount of amniotic fluid causing organization of the tissue, and the necrotic tissues may form a tight connection with the uterine wall and cannot be completely detached from the uterine wall, which can lead to difficulty in scraping or hemorrhage after the scraping procedure [ 3 ]. If the pregnancy tissue remains in the uterine cavity for a longer period of time, it can also lead to tissue lysis and release of large amounts of hemolysin into the blood circulation of the pregnant woman, causing a coagulation disorder, which can cause massive uterine bleeding and even lead to diffuse intravascular coagulation [ 4 ]. Therefore, the use of medications or other treatments to promote the release of mechanized placental tissue from the uterine wall prior to cleansing surgery becomes crucial in the treatment of MA.…”
Section: Introductionmentioning
confidence: 99%
“…(21). Also, in the study of Allameh et al, there was no significant relationship between the group receiving Miso and the group receiving Miso + letrozole (11).…”
Section: Discussionmentioning
confidence: 86%
“…It has been shown that in recent years, medical methods have been mostly used for abortions because this method is safer and more acceptable than surgical methods (8,9). One of the medical and medicinal approaches involves the use of prostaglandins, both alone and in combination with other medications (10,11). Miso is an analog of prostaglandin E1, which is prescribed for the prevention and treatment of gastric and duodenal ulcers (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…They reported rates of complete abortion of 80% and 51.8%, respectively, and an induction duration of 6.1 ± 1.6 and 9.4 ± 2.2 hours, respectively (P<0.05). Another study reported that the rate of complete abortion was 93.7% in the group taking 10 mg of letrozole daily for 3 days followed by 600 μg of oral misoprostol and 68.7% in the misoprostol only group [10] .…”
Section: A Comparative Study Between Methotrexate Versus Letrozole Pr...mentioning
confidence: 99%
“…By this drug, estrogen synthesis block leads to increase endogenous gonadotropin and finally stimulates growth of ovarian follicles, and also this drug could play a role in abortion therapy via inhibiting estrogen synthesis . This drug is also used to breast cancer related to estrogen [10] . Short time use of letrozole in inducing miscarriage had no severe consequences and its usual side effects are sweating, arthralgia, and fatigue, but could decrease bleeding resulted from medical miscarriage [11] .…”
Section: A Comparative Study Between Methotrexate Versus Letrozole Pr...mentioning
confidence: 99%